Creating a Homey Coffee Shop Concept in "Kedai Sepenuh Kopi" - Isfianadewi, Dessy; Anita Devi, Septianti (Archives of Business Research, 2022)
Service is the core product that provides essential consumer benefits. A business with excellence in service quality will increase customer satisfaction. This study aims to explain the company following the planning carried out by taking into account several aspects that have been previously analyzed and prove the feasibility analysis of the business that has been made goes according to plan. The method used is observation to see the development of Sepenuh Kopi as a new cafe in implementing its business. The results of this study reveal that business practices have been carried out well as a contemporary cafe project, starting from September 2019 to March 2022. In the current period in the first three months, namely September, October, and November, which is the initial introduction stage of Sepenuh Kopi as a newly established shop, the desired target consumer has not yet been achieved. However, the following month there was an increase and exceeded the desired sales target. The Covid-19 pandemic has caused sales to drop drastically. However, income gradually improved after making changes and holding a soft opening.